Real-world efficacy and safety of disitamab vedotin monotherapy or in combination with PD-1 inhibitors in locally advanced or metastatic upper tract urothelial carcinoma: a multicenter retrospective study - He, Shuaipeng; Wang, Cheng; Li, Xuan; Li, Can; Li, Dan; Zhang, Biao; Wan, Jianghou; Yue, Zhongjin; Wu, Gongjin; Zhang, Su; Ma, Junhai; Shang, Panfeng (Frontiers in Immunology, 2026)
ObjectiveDisitamab vedotin (RC48) is a HER2-targeted antibody–drug conjugate (ADC) that can induce immunogenic cell death and enhance antitumor immunity. Preclinical data suggest synergistic activity with PD-1 inhibitors, but its benefit in upper tract urothelial carcinoma (UTUC) remains unclear. This study evaluated the efficacy and safety of RC48, as monotherapy or combined with PD-1 blockade, in advanced UTUC.MethodsWe conducted a multicenter retrospective study of patients with locally advanced or metastatic UTUC treated with RC48 ± PD-1 inhibitors. Baseline features and adverse events (AEs) were summarized descriptively. Objective response rate (ORR) and disease control rate (DCR) were calculated with exact 95% confidence intervals. Progression-free survival (PFS) and overall survival (OS) were estimated by Kaplan–Meier and compared with the log-rank test. Multivariable Cox models included covariates significant in univariable analyses.ResultsA total of 41 patients were analyzed (9 monotherapy, 32 combination). Median follow-up was 16.5 months. The 12-month OS rate was 92.3%, and the 24-month OS rate was 63.2%; median OS was not reached. Median PFS was 12.6 months, with 6- and 12-month PFS rates of 78.0% and 56.4%, respectively. In an exploratory subgroup analysis, the 12-month PFS rate was 68.9% for first-line treatment versus 36.5% for later lines (p = 0.031). Among 22 patients with measurable lesions, ORR was 40.9% (9/22) and DCR was 81.8% (18/22). In the overall cohort of 41 patients, grade ≥3 AEs occurred in 18.8% (6/32) of patients in the combination group, including one grade 4 Stevens–Johnson syndrome.ConclusionRC48, used alone or in combination with PD-1 inhibitors, showed preliminary antitumor activity with manageable toxicity in patients with locally advanced or metastatic UTUC in this multicenter real-world cohort.